Clinical outcome of non-curative endoscopic submucosal dissection for early colorectal cancer. Issue 10 (20th January 2022) - Spadaccini, Marco; Bourke, Michael J; Maselli, Roberta; Pioche, Marhieu; Bhandari, Pradeep; Jacques, Jérémie; Haji, Amyn; Yang, Dennis; Albéniz, Eduardo; Kaminski, Michal Filip; Messmann, Helmut; Herreros de Tejada, Alberto; et al.
Abstract : Objective: Endoscopic submucosal dissection (ESD) in a curative intent for submucosa-invasive early (T1) colorectal cancers (T1-CRCs) often leads to subsequent surgical resection in case of histologic parameters indicating higher risk of nodal involvement. In some cases, however, the expected benefit may be offset by the surgical risks, suggesting a more conservative approach. Design: Retrospective analysis of consecutive patients with T1-CRC who underwent ESD at 13 centres ending inclusion in 2019 (n=3373). Cases with high risk of nodal involvement (non-curative ESD: G3, submucosal invasion>1000 µm, lymphovascular involvement, budding or incomplete resection/R1) were analysed if follow-up data (endoscopy/imaging) were available, regardless of the postendoscopic management (follow-up vs surgery) selected by the multidisciplinary teams in these institutions. Comorbidities were classified according to Charlson Comorbidity Index (CCI). Outcomes were disease recurrence, death and disease-related death rates in the two groups. Rate of residual disease (RD) at both the previous resection site and regional lymph nodes was assessed in the surgical cases as well as from follow-up in the follow-up group. Results: Of 604 patients treated by colorectal ESD for submucosally invasive cancer, 207 non-curative resections (34.3%) were included (138 male; mean age 67.6±10.9 years); in 65.2% of cases, no complete resection was achieved (R1). Of the 207 cases, 60.9% (n=126; median CCI: 3; IQR: 2–4) underwent surgical treatment with RD in 19.8% (25/126), while 39.1% (n=81, median CCI: 5; IQR: 4–6) were followed up by endoscopy in all cases. Patients in the follow-up group had a higher overall mortality (HR=3.95) due to non-CRC causes (n=9, mean survival after ESD 23.7±13.7 months). During this follow-up time, tumour recurrence and disease-specific survival rates were not different between the groups (median follow-up 30 months; range: 6–105). Conclusion: Following ESD for a lesion at high risk of RD, follow-up only may be a reasonable choice in patients at high risk for surgery. Also, endoscopic resection quality should be improved. Trial registration number: NCT03987828 .